Housing Programs for the Poor in Addis Ababa: Urban Commons as a Bridge between Spatial and Social. (November 2022) - Charitonidou, Marianna
The article presents the reasons for which the issue of providing housing to low-income citizens has been a real challenge in Addis Ababa during the recent years and will continue to be, given that its population is growing extremely fast. It examines the tensions between the universal aspirations and the local realities in the case of some of Ethiopia's most ambitious mass pro-poor housing schemes, such as the "Addis Ababa Grand Housing Program" (AAGHP), which was launched in 2004 and was integrated in the "Integrated Housing Development Program" (IHDP) in 2006. The article argues that the quotidian practices of communities and their socio-economic and cultural characteristics are related to the spatial attributes of co-housing practices. Drawing upon the idea that there is a mutual correspondence between social and spatial structures, it places particular emphasis on the analysis of the IHDP and aims to show that to shape strategies that take into account the social and cultural aspects of daily life of the poor citizens of Addis Ababa, it is pivotal to invite them to take part in the decision-making processes regarding their resettlement. Departing from the fact that a large percentage of the housing supply in Addis Ababa consists of informal unplanned housing, the article also compares the commoning practices in kebele houses and condominium units. The former refers to the legal informal housing units owned by the government and rented to their dwellers, whereas the latter concerns the housing blocks built in the framework of the IHDP for the resettlement of the kebele dwellers. The article analyzes these processes of resettlement, shedding light of the fact that kebele houses were located at the inner city, whereas the condominiums are located in the suburbs. Despite the fact that the living conditions in the condominium units are of a much higher quality than those in the kebele houses, their design underestimated or even neglected the role of the commoning practices. The article highlights the advantages of commoning practices in architecture and urban planning, and how the implementation of participation-oriented solutions can respond to the difficulties of providing housing. It argues that understanding the significance of the endeavors that take into account the opinions of dwellers during the phase of decision-making goes hand in hand with considering commoning practices as a source of architecture and urban planning frameworks for low-cost housing in this specific context. The key argument of the article is that urban planning and architecture solutions in Addis Ababa should be based on the principles of the so-called "negotiated planning" approach, which implies a close analysis of the interconnections between planning, infrastructure, and land.